"Just dreaming of them": The Berlin Project for Primary Prevention of Child Sexual Abuse by Juveniles (PPJ). (February 2016) - Beier, Klaus M.; Oezdemir, Umut C.; Schlinzig, Eliza; Groll, Anna; Hupp, Elena; Hellenschmidt, Tobias
Abstract: The Berlin Project for Primary Prevention of Child Sexual Abuse by Juveniles (PPJ) offers diagnostic and therapeutic help to 12-to-18-year-old juveniles with a sexual preference for the prepubescent and/or early pubescent body of children and who apply for treatment on a voluntary basis. The project goal is to prevent primary or recurrent child sexual abuse as well as primary or recurrent use of child abuse images. Treatment aims to enable affected juveniles to obtain control over their conflictual sexual behaviors. In the present article, the origin of the PPJ; its main approach, including the conception of a media campaign; as well as results from the first year of a three-year study are presented. Further, initial characterizations of juveniles taking part in the project for the first 12 months are provided. The results confirmed that the group of 12-to-18-year-old juveniles with a sexual preference for prepubescent and/or early pubescent minors exists as a target group for primary preventive measures and that they can be assessed for their sexual preferences.